CPLD based controller for single phase inverters - Saiman, Suhaimi (2007)
The DC-AC converter, also known as inverter, converts DC power to AC power at desired output voltage and frequency. The DC power input to the inverter is obtained from an existing power supply. Nowadays inverters use high power switching transistors either IGBT's and/or MOSFETs. In addition, the voltage and frequency of the source can be adjustable. These single phase inverters and their operating principles are analyzed in detail. In this project, a full-bridge, single phase inverter that uses a digital Pulse Width Modulation (PWM) to control the power switches at 18 kHz was constructed. The concept of PWM with different strategies for inverters is described. A type of filter is used to improve the distortion in the output waveform. A design and implementation of PWM by using complex programmable logic device (CPLD) from Altera MaxPlus II is constructed and programmed. The involved software, hardware, and suitable algorithm to implement and generate the PWM are developed in details. To verify the significant of this single phase inverter, the output voltage will be tested with resistive load and inductive load.